(untitled) (Journal of Human Sciences, 2022)
This research shows the role of the social work profession in reducing the phenomenon of crime in reform and rehabilitation institutions, as it is one fields of this profession. The problem of research has been derived from the existence of the criminal phenomenon in society and how to reduce it, so the social work has an important role in the reform and rehabilitation institutions. According to our experience and knowledge of the reality of some institutions, the social work is not available in these institutions. For that reason which prompted us to think about this issue. And the main goal in this research is to support and raise the level of societal recognition of the profession and its important role in addressing the criminal phenomenon. The question is about the role of the profession in reform and rehabilitation institutions, the problems faced by inmates, and the rehabilitation programs and methods offered to them. We answered the question in the research, and it is focused on the important aspect which is the professional practice of social work in reform and rehabilitation institutions, through the role of the social worker, by using professional methods, namely the case work, the social group work, and the organization work. And each of these methods has practical approaches that the social worker employs in working with the inmates, with the rehabilitation programs and the aftercare that the inmates should have, which is an important and complementary aspect of the reform process. The result of the study recommends the creation of social work offices in all institutions; in addition, raising the level of health and social services in them. It is also recommended that paying attention to workers as they are the actual agent for implementing the institution’s policy. The research suggests urging the competent authorities to prepare statistics and bulletins that enable the researchers to conduct studies on the criminal phenomenon, in order to reduce its risks and carry out awareness programs in particular. And work on studying housing plans in all cities and attaching them to recreational and cultural places for the population, and addressing middle educational institutions to educate students about falling into the clutches of criminal behavior, as they are the most affected age group. University and higher institutions have to be incited to prepare scientific cadres of social workers to work in this field and the various practical fields within society.